Study the Effect of Initial Temperature and Equivalence Ratio on the Pre – mixed Flame Propagation - Dakhil, Sadoun Fahad; Gabbar, Tahseen Ali (Basrah Journal for Engineering Sciences, 2012)
In this study a two dimensional, steady state propagation of the laminar premixed flame was numerically and experimental are investigated. The energy, momentum, continuity equations for species and global reaction mechanism with equation of stat for ideal gases were solved. Constant temperature boundary condition is applied on axi – symmetric in y – direction domain. The governing equations were discretized by using computation fluid dynamics (CFD) and finite-volume method - central differencing scheme, then solved using Gauss-Seidel Iteration method on uniformed grid with VISUAL BASIC code. Effects of equivalence ratio and initial temperature of fresh gases (air – fuel mixture) were investigated for three types of fuel Methane, Propane and Butane. Also the flame speed and flame temperature were experimentally measured for air – fuel (Methane, Propane, Butane and LPG) mixtures. The burning velocity was calculated depending on the flame speed and flame temperature measuring. The flame speed and flame temperature were measured by using optical technique. Effects of equivalence ratio and initial temperature of fresh gases (air – fuel mixtures) on flame speed and flame temperature are investigated experimentally. Results were generated for the detailed description of the local fluid flow and heat transfer characteristics including temperature, axial velocity, density and mole fractions profiles. For example the flame speed reached 274.4 cm/s as a maximum value at Ø=1.1 for propane air mixture, and flame temperature comparison give a good agreement between theoretical and experimental results at rich mixtyre